Impacts of microwave irradiation on the physical and chemical characteristics of virgin and pfoa-loaded granular activated carbons - UZUN, HABİBULLAH (My University, 2022)
In this study, the impact of MW irradiation on the physical and chemical characteristics of virgin and PFOA-loaded coal-based granular activated carbons (GACs) was assessed at various MW irradiation conditions (i.e., time, MW power) for different particle size of GACs at dry (i.e., as received/processed) and wet (i.e., soaked in distilled deionized water, DDW) conditions. Temperatures above 600 ℃ were reached in three minutes at MW power ≥250 Watt regardless of GACs type (bituminous coal vs lignite coal), particle size, and GAC irradiation condition (dry vs wet). Faster temperature rise was attained for dry than wet GACs. Temperature increased up to 3x faster for small particles (20-40 mesh) than virgin (raw, as received) of both GACs regardless of the irradiation condition (dry vs wet). Upon MW irradiation, the changes in physical characteristics (i.e., surface area, pore volumes (i.e., total, micro, and meso), and % weight loss) of GACs were higher for lignite coal-based than bituminous coal-based GAC. However, the physical characteristics of GACs were not impacted due to the GAC particle sizes or irradiation conditions (dry or wet) after MW irradiation. Zero-point charge pH (pHpzc) increased towards more basic surfaces after MW irradiation. After ten (10) cycles of MW irradiation (at a temperature of 600-800 ℃) of wet GAC samples, the variation of GAC surface area remained within 15%, while total and micropore volumes were within 22%. Five cyclic experiments (adsorption and successive MW regeneration) conducted using perfluoro octanoic acid (PFOA)-loaded GAC in a surface water demonstrated no major impact of MW regeneration on the physical and chemical features of GACs, and the PFOA adsorption capacity (~100%) remained as compared to the raw carbon.
Keywords: Çevre Mühendisliği; Çevre Teknolojisi; Mühendislik ve Teknoloji; Environmental Engineering; Environmental Technology; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Mühendislik, Bilişim ve Teknoloji (ENG); Çevre / Ekoloji; ÇEVRE BİLİMLERİ; Agriculture & Environment Sciences (AGE); Engineering, Computing & Technology (ENG); ENVIRONMENT/ECOLOGY; ENVIRONMENTAL SCIENCES; Doğa ve Peyzaj Koruma; Çevre Bilimi (çeşitli); Su Bilimi; Fizik Bilimleri; Yaşam Bilimleri; Nature and Landscape Conservation; Environmental Science (miscellaneous); Aquatic Science; Physical Sciences; Life Sciences; Granular activated carbons; Microwave irradiation; GAC regeneration; Perfluoro octanoic acid (PFOA)